Fatherhood in the Borderlands : A Daughter's Slow Approach. - Perez, Domino Renee (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture., 2022)
As a young girl growing up in Houston, Texas, in the 1980s, Domino Perez spent her free time either devouring books or watching films--and thinking, always thinking, about the media she consumed. The meaningful connections between these media and how we learn form the basis of Perez's "slow" research approach to race, class, and gender in the borderlands. Part cultural history, part literary criticism, part memoir, Fatherhood in the Borderlands takes an incisive look at the value of creative inquiry while it examines the nuanced portrayal of Mexican American fathers in literature and film. Perez reveals a shifting tension in the literal and figurative borderlands of popular narratives and shows how form, genre, and subject work to determine the roles Mexican American fathers are allowed to occupy. She also calls our attention to the cultural landscape that has allowed such a racialized representation of Mexican American fathers to continue, unopposed, for so many years. Fatherhood in the Borderlands brings readers right to the intersection of the white cultural mainstream in the United States and Mexican American cultural productions, carefully considering the legibility and illegibility of Brown fathers in contemporary media.